Efficacy and Tolerability of Malartin and Sulphadoxine-Pyrimethamine Combination against Uncomplicated Falciparum Malaria in Dibanda, Southwest Cameroon - Helen Kuokuo Kimbi; Mesame Ntoko; Nelson N. Ntonifor; Emmaculate Lum; Anna L. Njunda; Peter Nde Fon (Journal of Tropical Medicine)
Artemisinin derivatives are now the most potent and rapidly acting antimalarials. The aim of this study was to assess the in vivo efficacy and tolerability of a combination of Malartin (an artesunate) and sulphadoxine-pyrimethamine (SP) in the treatment of uncomplicated falciparum malaria in Dibanda, Cameroon. A total of 197 subjects were recruited into the study and administered Malartin for 3 days and SP as a single dose on day 0. Only 174 of the subjects were successfully followed up on days 3, 7, and 14. The overall success rate of the drug combination was 92.53%. Parasite density decreased during the follow-up period in different age groups, sexes, and social classes. The prevalence of anaemia decreased from 22.99% at enrolment to 9.77% on day 14, and the difference was significant (P<0.05) on all days of followup. The drug combination did not give rise to any serious side effects.